PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU BAHASA INGGRIS - Liasrawati Liasrawati; Zakaria Zakaria; Puspa Djuwita (Manajer Pendididikan, 2017)
The general purpose of the research is to describe about the role of leadership in improving english teacher performances. The research used qualitative descriptive method. The subjects of this research were principals, vice principal, english teachers at Junior High Shool Number 2 of South Bengkulu. The techniques of collecting data were observation, interview, and documentation study. The general result of the study show that the role of school principal in increasing english teacher capability was run well. The specific results were: The process of teaching and learning process by the english teacher was done perfectly, the english teacher competence was increased, the quality of  english teacher work was done continually.